Respuesta :

leena

Hello!

[tex]\large\boxed{x = 2}[/tex]

Solve the system using substitution:

We can rearrange the second equation to find an expression for y:

x - y = 3

Subtract x from both sides:

-y = -x + 3

Multiply the equation by -1:

y = x - 3

Substitute this value of y into the first equation:

4x + 2y = 6

4x + 2(x - 3) = 6

Distribute:

4x + 2(x) + 2(-3) = 6

Simplify and combine like terms:

4x + 2x - 6 = 6

6x = 12

6x / 6 = 12 / 6

x = 2.

Answer:

y = -1

Step-by-step explanation:

x - y = 3

x = 3 + y

4x + 2y = 6

substitute x for 3 + y

4(3+y) + 2y = 6

open the parenthesis

12 + 4y + 2y = 6

12 + 6y = 6

subtract 12 from both sides of the equation

12 - 12 + 6y = 6 - 12

6y = 6 - 12

6y = -6

divide both sides of the equation by 6

6y/6 = -6/6

y = -6/6

y = -1

ACCESS MORE